Association between life’s essential 8 and periodontitis: a study based on NHANES 2009–2014 - Hou, KeGui; Zhang, Hongli; Song, Wenpeng; Li, Shi; Liu, JiaRui; Ma, Zhaofeng (Frontiers in Medicine, 2024)
Background This research aims to investigate the relationship between Life’s Essentials 8 (LE8), the American Heart Association’s latest indicator, and periodontitis. The purpose is to provide guidance on preventative measures. Methods Data for our investigation were obtained from the National Health and Nutrition Examination Survey (NHANES) 2009–2014, with a total of 8,784 participants eligible. LE8 scores were compiled from 8 index scores (the score for each component of diet, physical activity, nicotine exposure, sleep duration, body mass index, blood lipids, blood glucose, and blood pressure). Periodontitis was classified by the Centers for Disease Control and Prevention and American Academy of Periodontology (CDC/AAP). The study utilized multivariable logistic analyses to investigate the potential correlation. Results After controlling for all covariates, LE8 was discovered to have a significant negative correlation with periodontitis prevalence [0.91 (0.88, 0.94)]. This trend continued to hold statistical significance even after converting LE8 into a categorical variable. Furthermore, a noteworthy adverse correlation was discovered across both genders, specifically males [0.35 (0.22, 0.55)] and females [0.39 (0.25, 0.60)], as well as for the majority of categorical classifications, namely ethnicity, age, education level, and marital status. However, only the age subgroups displayed some degree of significant difference from each other. Conclusion Life’s essential 8 was negatively associated with periodontitis, but more prospective trails are needed to confirm our findings.